Studies on the complexes of Si(IV), Sn(IV), Ti(IV), Zr(IV) and Hf(IV) chlorides with 1, 1 Bis (Thiocyanato mercurio) ferrocene. - Dixit, Vivek (International Multidisciplinary Research Journal, 2012)
Silicon (IV), tin(IV), titanium(IV), Zirconium(IV) and Hofnium(IV) from 1:1 and 1:2 adducts with number of monodentate & bidentate ligands[1-5]. No attempt has been made to react ferrocene derivative with these tetravalent lewis acids. In recent years ferrocene derivatives have been used as bases[6-7] towards certain metal ions but not towards group four tetrachlorides. In this paper I present study on a new series of complexes prepared from ferrocene derivatives with tetrachlorides of Si, Sn, Ti, Zr & Hf. Â 